Slurry-Based Processing of Solid Electrolytes: A Comparative Binder Study. Issue 16 (22nd December 2018) - Riphaus, Nathalie; Strobl, Philipp; Stiaszny, Barbara; Zinkevich, Tatiana; Yavuz, Murat; Schnell, Joscha; Indris, Sylvio; Gasteiger, Hubert A.; Sedlmaier, Stefan J.
Abstract : Limited energy density of today's Li-ion battery technologies demands for novel cell technologies, such as the all-solid-state battery (ASSB). In order to achieve high energy densities and enable large-scale processing, thin and flexible solid electrolyte (SE) layers have to be implemented. This study focuses on slurry-based processing of the sulfidic solid electrolyte Li10 SnP2 S12 (LSPS). Various polymers were investigated concerning their suitability as binders for thin and freestanding SE sheets. We conducted a parameter study in order to optimize e.g. LSPS-to-binder ratio, solids content and porosity. Significant differences were found with regard to the minimum amount of binder required for mechanically stable sheets as well as the homogeneity, density and flexibility of the resulting SE layers. The impacts of binder type and weight fraction on ionic conductivity were examined through lithium diffusion measurements. Impedance analysis was conducted in comparison, proving sufficiently high ionic conductivity for potential application of the SE sheets in ASSB. This work highlights the important role of the polymeric binder in slurry-based processing of SEs and gives an impression how important a well-considered selection of parameters is to achieve good processing properties as well as desirable features for the final SE sheet.